Civil society and anti-corruption reform in Georgia: revisiting the rose revolution - Aprasidze, David (Frontiers in Political Science, 2025)
This article revisits the role of civil society in Georgia’s Rose Revolution of 2003 and its aftermath, with a particular focus on the dynamics of anti-corruption reform. While much of the existing scholarship frames the Rose Revolution within the paradigm of democratic transition and top-down institutional reform, this study highlights the underexplored contribution of civil society actors—organizations, activists, and experts—across three phases of political reconfiguration: before, during, and after the uprising. Drawing on secondary sources, media analysis, and in-depth interviews, the article argues that civil society was not merely a catalyst of mass mobilization but an active agent in shaping both the revolutionary process and subsequent policy outcomes. Prior to the revolution, civil society actors were key in reframing public discontent around issues of corruption. During the uprising, they forged alliances with reformist political forces and played a central role in election monitoring and protest coordination. After the regime change, civil society’s influence evolved through the transfer of expertise, personnel, and policy agendas into state institutions. While this institutionalization came at the cost of watchdog independence, it also enabled the implementation of swift and effective reforms. The article contributes to broader debates on civil society’s dual role as both a driver of democratic contestation and a partner in governance, particularly in post-revolutionary and transitional settings.